Optimalisasi Pengelolaan BUMNag Duo Baleh Suku Melalui Pelatihan Manajemen Bisnis dan Keuangan - Yuliarti Yuliarti; Hidayatul Fajri; Iip Permana; Artha Dini Akmal (Jurnal Pengabdian UNDIKMA, 2023)
This service program aims to increase the knowledge and capacity of BUMNag Duo Baleh Suku managers regarding business management competence and financial governance of village-owned enterprises. The method used in implementing this community partnership service is Participatory Learning Action (PLA). While the activity implementation technique is offline, with several stages, namely the preparation stage, the implementation stage and the monitoring and evaluation stage. The instrument for evaluating this activity is through questionnaires and interviews which are analyzed descriptively. The results of this dedication show that there is an increase in the capacity of BUMNag Duo Suku managers in business management and financial governance. In making decisions, management is able to read market orientation while still minimizing production costs without reducing quality. For financial governance along with the preparation of financial reports (cash flow statements, profit and loss statements and company balance sheets) made by the treasurer already follow the SAK financial accounting standards and are made using Microsoft Excel.